Simulation of Surface Segregation in Nanoparticles of Pt-Pd Alloys - Jose Brito Correia; Ana Isabel de Sá (Crystals)
Platinum (Pt) and palladium (Pd) are crucial in hydrogen energy technologies, especially in fuel cells, due to their high catalytic activity and chemical stability. Pt-Pd nanoparticles, produced through various methods, enhance catalytic performance based on their size, shape, and composition. These nanocatalysts excel in direct methanol fuel cells (DMFCs) and direct ethanol fuel cells (DEFCs) by promoting alcohol oxidation and reducing CO poisoning. Pt-Pd catalysts are also being explored for their oxygen reduction reaction (ORR) on the cathodic side of fuel cells, showing higher activity and stability than pure platinum. Molecular dynamics (MD) simulations have been conducted to understand the structural and surface energy effects of PdPt nanoparticles, revealing phase separation and chemical ordering, which are critical for optimizing these catalysts. Pd migration to the surface layer in Pt-Pd alloys minimizes the overall potential energy through the formation of Pd surface monolayers and Pt-Pd bonds, leading to a lower surface energy for intermediate compositions compared to that of the pure elements. The potential energy, calculated from MD simulations, increases with a decreasing particle size due to surface creation, indicating higher reactivity for smaller particles. A general contraction of the average distance to the nearest neighbour atoms was determined for the top surface layers within the nanoparticles. This research highlights the significant impact of Pd segregation on the structural and surface energy properties of Pt-Pd nanoparticles. The formation of Pd monolayers and the resulting core–shell structures influence the catalytic activity and stability of these nanoparticles, with smaller particles exhibiting higher surface energy and reactivity. These findings provide insights into the design and optimization of Pt-Pd nanocatalysts for various applications.